Analisis Faktor Kesulitan Belajar Matematika pada Materi Bangun Ruang di Kelas V SD Negeri 17 Air Salek - veronica, Nina; Arafat, Yasir; Tanzimah, Tanzimah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The research was conducted with the aim of describing the factors that cause learning difficulties in mathematics for fifth grade students of SD Negeri 17 Air Salek. This study uses questionnaires, interviews, and documentation instruments that discuss the factors of learning difficulties experienced by students. Based on the results of the research on the analysis of the difficulty of learning mathematics in building materials in class V of SD Negeri 17 Air Salek, it can be ascertained that, the factor of learning difficulties in mathematics in the material of building spaces in class V of SD Negeri 17 Air Salek consists of 2 factors, the first is internal and external factors. external. learning difficulty factors consisting of internal factors consisting of students' self and external factors consisting of outside students in class V SD Negeri 17 Air Salek were 81% included in the very valid category. There are 8 subjects who are not interested in learning mathematics, 7 subjects are not interested in learning mathematics and 5 subjects are not able to learn mathematics.